2019
DOI: 10.3800/pbr.14.320
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal distribution of environmental DNA derived from Japanese sea nettle jellyfish <i>Chrysaora pacifica</i> in Omura Bay, Kyushu, Japan

Abstract: We surveyed the spatial and temporal distribution of Japanese sea nettle jellyfish Chrysaora pacifica in Omura Bay, Japan, using an environmental DNA (eDNA) method. In 2018, the C. pacifica eDNA concentration increased from March-May at all depths. The seasonal pattern of C. pacifica eDNA was consistent with previous reports based on visual observations along the Japanese coast. Thus, the eDNA method might have advantages to follow the seasonal pattern of C. pacifica while being less time-consuming and less la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Of note, the concentrated aggregation detected in depth around 40m in certain sampling locations was not detected in the surface waters. This is in line with recent studies which showed eDNA dispersal was restricted by halocline [37] and pycnocline [38] using eDNA surveys. The vertical distribution of eDNA depends on the layer where the organism resides and the dispersion and degradation of eDNA [2].…”
Section: Vertical Distribution Of L Polyactissupporting
confidence: 93%
“…Of note, the concentrated aggregation detected in depth around 40m in certain sampling locations was not detected in the surface waters. This is in line with recent studies which showed eDNA dispersal was restricted by halocline [37] and pycnocline [38] using eDNA surveys. The vertical distribution of eDNA depends on the layer where the organism resides and the dispersion and degradation of eDNA [2].…”
Section: Vertical Distribution Of L Polyactissupporting
confidence: 93%
“…The implementation of eDNA for surveying GZP biodiversity has been integrated within broader assessments of marine biodiversity, including zooplankton in coral reefs in Florida (Djurhuus et al., 2018), as a part of a mesozooplankton survey in the Western Pacific (Feng et al., 2022) and in the mesopelagic zone in the North‐Atlantic (Govindarajan et al., 2021). Studies with a focus on single‐species GZP detection have been increasing in number in temperate and tropical areas including scyphozoan species in the Sea of Japan (Minamoto et al., 2017; Ogata et al., 2021; Takasu et al., 2019), and cubozoans (Bolte et al., 2021; Morrissey et al., 2022). However, the use of eDNA metabarcoding studies truly focused on jellyfish biodiversity and at the community level are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study compared the zooplankton taxa recovered with nets and with eDNA of filtered water samples, and demonstrated eDNA to be particularly suitable for revealing gelatinous diversity (Govindarajan et al, 2021). However, eDNA studies focusing on gelatinous zooplankton still remain relatively scarce (Ames et al, 2021;Gaynor et al, 2017;Minamoto et al, 2017;Takasu et al, 2019).…”
Section: The Elusive Rare and Endangered: Edna As A Non-invasive Methodsmentioning
confidence: 99%